Coordination Between Partial Robotic Exoskeletons and Human Gait: A Comprehensive Review on Control Strategies - Lora-Millan, Julio S.; Moreno, Juan C.; Rocon, E. (Frontiers in Bioengineering and Biotechnology, 2022)
Lower-limb robotic exoskeletons have become a reality as powerful tools to assist or rehabilitate the gait in impaired subjects, even when they are designed to act partially over the locomotor system of the users, as in the case of unilateral or single-joint exoskeletons. These partial exoskeletons require a proper method to synchronize their assistive actions with the user’s gait and ensure the correct inter-joint coordination. This review analyzes the state of the art of control strategies used to coordinate the assistance provided by the device with the actual gait of the wearer. We have analyzed and classified the different approaches independently of the hardware implementation, describing their basis and principles. We have also reviewed the experimental validations of these devices for healthy and impaired subjects to provide the reader with a clear view of their technology readiness level. Eventually, the current state of the art and necessary future steps in the field were summarized and discussed.